ANALISIS PELATIHAN KETERAMPILAN WIRAUSAHA BAGI PENYANDANG DISABILITAS TUNANETRA DI SLB-A KARYA MURNI MEDAN - Sara Oktavia Purba; Vidya Dwi Amalia Zati; Fauzi Kurniawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Individuals with visual impairments often face various challenges in obtaining formal employment due to limited access to the labor market, low levels of social acceptance, and a lack of job opportunities that match their abilities. Therefore, entrepreneurial skills serve as an alternative means of improving their economic independence. This study aims to analyze entrepreneurship skills training for visually impaired individuals at SLB-A Karya Murni Medan, focusing on the aspects of planning, implementation, and the supporting and inhibiting factors of the training program. This research employed a descriptive qualitative method with an approach that emphasizes in-depth observation of the phenomenon under study. Data were collected through observations, interviews, and documentation to obtain a comprehensive understanding of the implementation of entrepreneurship skills training.The findings reveal that the planning of the entrepreneurship training program was conducted systematically through the identification of participants’ needs, the determination of training objectives, the preparation of learning materials, and the provision of facilities and infrastructure tailored to the conditions and needs of visually impaired individuals. The implementation of the training was carried out effectively through direct practice, demonstrations, and individual mentoring, which successfully enhanced participants’ knowledge, skills, and self-confidence. Supporting factors included the commitment of the management, instructors, and mentors, participants’ motivation, and a conducive learning environment. Meanwhile, inhibiting factors consisted of limited funding, inadequate facilities and infrastructure, a shortage of instructors, and restricted access to product marketing. Overall, the entrepreneurship skills training program at SLB-A Karya Murni Medan has made a positive contribution to improving the skills and independence of visually impaired individuals, providing them with valuable preparation for entering the workforce and establishing independent businesses.